Excited states. - Lim, Edward C., 1932- (Academic Press, 1974)
Excited States, Volume I reviews radiationless transitions, phosphorescence microwave double resonance through optical spectra in molecular solids, dipole moments in excited states, luminescence of polar molecules, and the problem of interstate interaction in aromatic carbonyl compounds. The book discusses the molecular electronic radiationless transitions; the double resonance techniques and the relaxation mechanisms involving the lowest triplet state of aromatic compounds; as well as the optical spectra and relaxation in molecular solids. The text also describes dipole moments and polarizab.